Environmental Management at the Interuniversity Headquarters through the Environmental Advisory Team and the Environmental Award Program - Ruiz Siles, Yanina (2022)
The research has shown that, despite the administrative differences of the different state universities, the Equipo Asesor Ambiental (EAA) has achieved interuniversity participation and collaboration in environmental matters, allowing innovation processes in this area. To this end, it aims to analyze the work of the EAA and the integration of the Sede Interuniversitaria de Alajuela (SIA), generating data that allow replicating this relationship in other spaces. Due to the mixed nature of the establishment, it was decided to focus on the Environmental Award program, which will deepen this process. The information was collected from official sources, such as the EAA and the UCR. It was determined that the integration of different entities and the community play a fundamental role in environmental management. The advances of the SIA-UCR have contributed to the development of new projects, as well as others have been adapted to the specificities of the SIA and the context. An investigation of this type of link is strategic, since it allows us to understand and reflect on the role that environmental management programs could play in different areas.